THE INTREPRETATION OF A WORD OR POETRY IN MATNAZAR ABDULHAKIM’S JOURNALISM - H. Q. Gaipova (Journals Park Publishing, 2022)
In this article are highlighted journalistic views about literary words and poetry in the literary thoughts janre of well-known poet M. Abdulhakim
Keywords: journalistic; literary thought; artistic word